Pengaruh Customer Experience, Place Attachment, Customer Satisfaction, dan Word-of-Mouth terhadap Revisit Intention Konsumen Restoran Ayam Cepat Saji asal Amerika - Amin Tatik Uswatun Khasanah; Hasti Oktafiani; Shelylla Aprilydia Putri; Wati Anggraini; Usep Suhud (Jurnal Bisnis, Manajemen, dan Keuangan, 2020)
This study aims to examine the factors that influence revisit intention in the American fast food chicken restaurant. In this case, there are four variables used to measure, namely customer experience, place attachment, customer satisfaction and word-of-mouth. Data collection using online questionnaire and respondents were selected using a convenience sampling technique. The total respondents in this study were 253 consisting of 48 men and 205 women. Data were processed using exploratory factor analysis and structural equation models. The result, customer experience has a positive and significant effect on revisit intention, word of mouth has a positive and significant effect on revisit intention. While place attachment variable does not have a significant effect on revisit intention and customer satisfaction does not have a significant effect on word-of-mouth.